‏ ‏The‏ ‏Semantic of ‘Request’ Past form in the Standard Arabic, and the ‎‏ ‏Torah’s ‎Hebrew, a Comparative Study - Alna` naa`i, Tarek S. M. S.; Al-Dawoodi, Zahir bin Marhoon; Al-Riyami, Mahmood bin Sulaiman (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to examine past-tense forms expressing requests in both Arabic and Hebrew, identifying the similarities and differences between the two languages. It seeks to categorize the various forms of past-tense requests and the meanings they have evolved into. Additionally, the study emphasizes the importance of incorporating this grammatical form into Arabic and Hebrew morphology and syntax textbooks. Methods: The study employs a comparative approach, analyzing Arabic and Hebrew—two languages originating from the same Semitic root. Results: The two languages show both similarities and differences. Among the similarities, both languages use the past tense to convey a present or imperative request, including meanings such as supplication, offer, and exhortation. Both also use the past tense after a question to express prohibition. However, the languages differ in their use of the conversive vav in the Torah, a feature absent in Classical Arabic. Additionally, Arabic differs from Hebrew in expressing offer or exhortation after lawla or without it. Conclusions: The past tense conveys the meanings of present-tense requests and commands in both languages and also expresses prohibition, supplication, offer, and exhortation. The Torah differs from the Quran and Classical Arabic in its use of the conversive vav. Moreover, the Quran often omits particles of meaning to convey various requests, and the imperative present tense in Arabic is marked by the prefix lam, a feature absent in Hebrew.